Learning Outcomes and Critical Thinking Increased: Study on Junior High School Students using Combination of PBL Model with Quizziz - Musdalifah, Nuril Huda, Sunardjo (Lembaga Bale Literasi, 2025)
What kids learn and how well they can think critically are both significantly impacted by the learning paradigm that is implemented. Nevertheless, there is still a lack of widespread use of the PBL paradigm in conjunction with Quizziz. The effects of the Quizizz-based problem-based learning paradigm on the critical thinking and learning outcomes of SMPN 1 Kamal eighth graders are examined in this study. This study used a quantitative research approach, employing a quasi-experimental design, to find out how the problem-based learning (PBL) model affected the learning outcomes and critical thinking of students at SMPN 1 Kamal, as well as their levels of learning motivation and material comprehension. Utilising the statistical tests available in the IBM SPSS v.20.1 program, the collected data will be examined for validity, reliability, normalcy, and multivariate analysis of variance (MANOVA). Based on the significance value of 0.002, which is less than 0.05, the hypothesis testing analysis using multivariate MANOVA on student learning outcomes and creativity indicates that the problem-based learning model with Quizizz as an aid significantly impacts student learning outcomes and critical thinking in the eighth grade at SMPN 1 Kamal.